Identifikasi Pola Iris Menggunakan Metode Backpropagation - Yoan Elviralita; Asrul Hidayat (Manutech : Jurnal Teknologi Manufaktur, 2016)
In recent years, there has been a lot of research related to pattern recognition is conducted to identify various forms of patterns and controlling system. Utilizing backpropagation neural network in pattern identifying is very useful to solve problems with unknown parameter and difficult to determined. And then the data of the pattern are trained and tested. The results obtained from the recognition rate indicates a backpropagation neural network, provide excellent performance, which is an average of 98%. This neural network is expected to be developed by other researchers for the advancement of knowledge in all fields.